Charge Transport: Enhanced Vertical Charge Transport of Homo‐ and Blended Semiconducting Polymers by Nanoconfinement (Adv. Mater. 10/2020). Issue 10 (9th March 2020) - Ko, Jongkuk; Kim, Youngkeol; Kang, Jin Soo; Berger, Rüdiger; Yoon, Hyunsik; Char, Kookheon
Abstract : In article number 1908087, Rüdiger Berger, Hyunsik Yoon, Kookheon Char, and co‐workers demonstrate the versatility of nanoconfinement on various semiconducting polymers for enhancing vertical charge transport. Both homogeneous and blended semiconducting polymers show more than two orders of magnitude higher charge mobility along the out‐of‐plane direction due to the enhanced crystallinity and compatibility of the polymers through the polymer assembly under nanoconfined geometries.